Risk-return performances of real estate investment funds in Turkey including the Covid-19 period - Çamlibel, Mehmet Emre; Sümer, Levent; Hepşen, Ali (International Journal of Strategic Property Management, 2021)
The purpose of this research is to give an insight into the Turkish real estate investment funds (T-REIFs) by comparing their risk-return performances with the main benchmark investment tool Istanbul Stock Exchange-100 (BIST-100) Index. This study evaluated the performance of T-REIFs in four different periods between January 2017 and December 2020 (2017m1–2017m12, 2018m1–2018m12, 2019m1–2019m12 and 2020m1–2020m12) including the Coronavirus Disease (Covid-19) period by applying the Sharpe and Treynor ratios. In a well-diversified portfolio both ratios give the same results, but in the presence of non-systematic risk and the portfolio is poorly diversified, the Treynor ratio is a better indicator than the Sharpe ratio. The findings of this study show that rankings of Sharpe and Treynor ratios may differ for each period. These results also support the fact that the portfolios of funds in the Turkish real estate market are not well diversified. By providing corporate tax exemptions, and by enabling the investors to diversify their investments and reduce their risks, real estate investment funds are important alternatives to direct real estate investments in Turkey. In that context, being one of the pioneer studies in this niche and a new topic in emerging markets, analyzing the return performances of T-REIFs and comparing them with the returns of the BIST-100 index is aimed to contribute to literature as well as provide insight to investors who may consider investing in the Turkish real estate capital market instruments.